2006
DOI: 10.1152/ajpendo.00608.2004
|View full text |Cite
|
Sign up to set email alerts
|

Physical training reverses the increased activity of the hepatic ketone body synthesis pathway in chronically diabetic rats

Abstract: This study was designed to examine whether the training-induced improvement in the plasma concentration of ketone bodies in experimental diabetes mellitus could be explained by changes in the activity of the hepatic ketone body synthesis pathway and/or the plasma free fatty acid levels. Diabetes mellitus was induced by an intravenous injection of streptozotocin (50 mg/kg), and training was carried out on a treadmill. The plasma concentration of ␤-hydroxybutyric acid was increased (P Ͻ 0.001) in sedentary diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Moreover, exercise training also exhibited an inhibitory effect on hepatic ketone synthesis and a stimulatory effect on muscle ketone use. These observations confirm the previous reports in diabetic rat model that exercise training can lower ketone body concentration through a combination of lower NEFA levels, decreased hepatic ketone synthesis [10], and enhanced muscle ketone utilization pathway [9]. However, ketone body use referred to here is ketone body oxidation, i.e.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, exercise training also exhibited an inhibitory effect on hepatic ketone synthesis and a stimulatory effect on muscle ketone use. These observations confirm the previous reports in diabetic rat model that exercise training can lower ketone body concentration through a combination of lower NEFA levels, decreased hepatic ketone synthesis [10], and enhanced muscle ketone utilization pathway [9]. However, ketone body use referred to here is ketone body oxidation, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, exercise training is reported to reduce plasma FFA and β-hydroxybutyric acid levels in a rat model of diabetes induced by streptozotocin (STZ) [8][9][10], through a reversal of defective activity of 3-ketoacyl-CoA transferase in muscle ketone use [9], and a decrease in the overall activity of ketone synthesis pathway in the liver [10].…”
mentioning
confidence: 99%
“…On the other hand, studies performed in rats (2) have demonstrated that the ketone body production is elevated in isolated hepatocytes from nonobese diabetic animals. More importantly, we have demonstrated that physical training reverses the increased activity of the hepatic ketone body synthesis pathway in chronically diabetic rats (12).…”
Section: Discussionmentioning
confidence: 75%
“…Upregulation of the hepatic ketone body synthesis pathway is induced in diabetes, and as expected, chronic insulin deficiency in rats accordingly yields a substantial increase in both plasma free fatty acids and -hydroxybutyric acid concentrations [55]. In a series of studies by Midaoui et al [55,56], plasma concentrations of -hydroxybutyric acid in diabetic rats may be reduced with physical training despite any notable changes in plasma glucose or insulin levels. This exercise-incited reduction in circulating concentrations of ketone bodies has been attributed to decreased production in the liver or increased uptake by peripheral tissues.…”
Section: Lipid and Ketone Metabolism In The Exercise-trained Diabeticmentioning
confidence: 84%
“…In spite of this, Ohmori et al have strongly correlated habitual exercise with the marked reduction of plasma ketone bodies and glucagon in mildly diabetic rats and plasma ketone bodies, particularly acetoacetate, in severely diabetic rats [54]. Upregulation of the hepatic ketone body synthesis pathway is induced in diabetes, and as expected, chronic insulin deficiency in rats accordingly yields a substantial increase in both plasma free fatty acids and -hydroxybutyric acid concentrations [55]. In a series of studies by Midaoui et al [55,56], plasma concentrations of -hydroxybutyric acid in diabetic rats may be reduced with physical training despite any notable changes in plasma glucose or insulin levels.…”
Section: Lipid and Ketone Metabolism In The Exercise-trained Diabeticmentioning
confidence: 99%